2016
DOI: 10.1016/j.jinsphys.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the secreted watery saliva proteins of the rice brown planthopper, Nilaparvata lugens (Stål) by transcriptome and Shotgun LC–MS/MS approach

Abstract: The rice brown planthopper, Nilaparvata lugens (Stål), a major rice insect pest in Asia, is a vascular bundle-feeder that ejects gelling and watery saliva during the feeding process. Although major proteins in the salivary glands of N. lugens have been identified using 2D PAGE, very little is known about the secreted saliva of this insect. In this study, we identified the major proteins in the secreted watery saliva of N. lugens, via collecting from a sucrose diet that adult planthoppers had fed upon through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 69 publications
1
64
0
Order By: Relevance
“…Some repeated amino acid sequences, a typical feature of mucin-like proteins (Verma and Davidson, 1994), were found. NlMLP protein has been detected in both gelling and watery saliva Liu et al, 2016). To investigate the functions of NlMLP, we analyzed mRNA levels in BPHs at various developmental stages, including eggs, first to fifth instar BPHs, and female and male adults, via quantitative reverse transcription (qRT)-PCR.…”
Section: Nlmlp Is Highly Expressed In N Lugens Salivary Glands and Smentioning
confidence: 99%
See 1 more Smart Citation
“…Some repeated amino acid sequences, a typical feature of mucin-like proteins (Verma and Davidson, 1994), were found. NlMLP protein has been detected in both gelling and watery saliva Liu et al, 2016). To investigate the functions of NlMLP, we analyzed mRNA levels in BPHs at various developmental stages, including eggs, first to fifth instar BPHs, and female and male adults, via quantitative reverse transcription (qRT)-PCR.…”
Section: Nlmlp Is Highly Expressed In N Lugens Salivary Glands and Smentioning
confidence: 99%
“…Like other piercing-sucking insects, BPHs secrete gelling and watery saliva. Recently, genomic tools such as proteomics and transcriptomics have been used to investigate BPH salivary glands and saliva at the molecular level (Konishi et al, 2009;Ji et al, 2013;Huang et al, 2016;Liu et al, 2016). Two secretary proteins that actively participate in salivary sheath formation were recently identified in BPHs (Huang et al, 2015.…”
mentioning
confidence: 99%
“…Here, we reveal that the planthopper saliva can degrade DNA, and that the responsible enzyme is DNase II. In a previous study, the presence of salivary DNase II has been reported in the white‐backed planthopper (Huang et al ., ; Miao et al ., ), brown planthopper (Liu et al ., ; Huang et al ., ), and SBPH (Huang et al ., ). Although the composition of the saliva has been reported in > 10 Aphididae species, no salivary DNase II was found in these phloem‐feeding aphids (van Bel & Will, ), which deserved further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila melanogaster , DNase II is thought to have roles similar to those in C. elegans (Evans et al ., ). Surprisingly, DNase IIs have been found to be abundantly and ubiquitously distributed in the saliva of three planthoppers (Liu et al ., ; Huang et al ., ; Miao et al ., ) and two spider mite species (Huang et al ., ; Zhu et al ., ). However, the precise functions of these salivary DNase IIs remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, various salivary components may play important roles in feeding on host plants [5]. To date, extensive data have accumulated on the salivary gland transcriptome and proteome of vascular tissue-feeding hemipteran species, including the transcriptomes of Empoasca fabae Harris [6] and Nilaparvata lugens (Stål) [7] and the proteome of Acyrthosiphon pisum (Harris) [8, 9]. Although numerous salivary genes and proteins have been identified, functionally, only a few of them have been characterized [10].…”
Section: Introductionmentioning
confidence: 99%